Protection Of Food From Fungal Pathogens A Review - Ijaz, Sara; Maryam, Uswa; Zubair, Nimra (Green Publisher Indonesia, 2022)
The profitability, quality, and output volume of plant production is significantly influenced by plant fungal diseases. These phytopathogens are persistent in getting past plant defences, which leads to diseases and quality losses that cost the US economy billions of dollars every year. Farmers have employed fungicides to manage the damage caused by plant pathogenic fungus in order to combat the epidemic of fungal plant diseases. Researchers and growers are looking for alternate solutions because of drawbacks including resistance development and environmental damage linked to these drugs. Materials and Procedures Using the search terms